Circulating Irisin as a Potential Diagnostic and Vascular Protective Biomarker in Patients with Metabolic Syndrome - Rashid, Rayah Najat; Saleh, Ahmed Hamad (American Journal of Biology and Natural Sciences, 2026)
Background & Aims: Metabolic syndrome (MetS) is a multifaceted metabolic disorder characterized by an increased cardiovascular risk and endothelial dysfunction. Recently, it has become increasingly apparent that myokines from skeletal muscle may have profound effects on metabolism and vascular tone. The aim of the present study is to assess the diagnostic potential of circulating Irisin and its association with oxidative stress, vascular function and metabolic profile in MetS. Materials and Methods: One hundred fifty-six subjects were included, consisting of 78 patients with MetS and 78 age-matched healthy control subjects. The anthropometric measurements and blood pressure were also measured. Plasma contents of Irisin, Myostatin, FGF-21, malondialdehyde (MDA) and nitric oxide (NO) were assayed ELISA methods. HOMA-IR was used to evaluate the extent of insulin resistance. Results: MetS patients had significantly higher BMI (31.8 ± 4.5 vs 23.4 ± 2.1 kg/m²), waist circumference (104.5 ± 9.2 vs 84.2 ±6.1 cm) and blood pressure (p <0..05). Serum Irisin was significantly lower in MetS patients (6.2 ± 1.5 vs. 12.4 ± 2.8 ng/mL; p <0.001), whereas serum Myostatin and FGF-21 were higher than in controls. Oxidative stress was also augmented as observed by higher MDA concentrations (4.2 ± 0.9 vs 1.8 ± 0.4 µmol/L) and decreased availability of NO (18.4 ± 3.1 vs 35.8 ± 5,2 µmol/L, p < 0,001). Irisin was found to be significantly negatively correlated with BMI (r = −0.425), HOMA-IR (r = −0.512) and MDA (r = −0.621) and positively with NO (r= 0.582, p < 0.001). ROC analysis showed that the diagnostic performance of Irisin for MetS was excellent (AUC = 0.89, sensitivity = 85.9%, specificity = 82.1%). Conclusions: Low circulating Irisin levels are strongly related to metabolic disarrangement, oxidative stress and endothelial dysfunction in MetS. Irisin might be taken as a potential diagnostic and protective biomarker of metabolic syndrome.